Risk Aversion and the Subjective Time Discount Rate: A Joint Approach - Bernard M.S. van Praag; Adam S. Booij (Tinbergen Institute, 2003)
In this paper we analyze a large sample of individual responses to six lottery questions. Wederive a simultaneous estimate of risk aversion ? and the time preference discount rate ? perindividual. This can be done because the consumption of a large prize is smoothed over a largertime period. It is found that ? and ? strongly vary over individuals, while they are negativelycorrelated with a correlation coefficient of -.3. Furthermore we explain ? and ? by income,age, gender, entrepreneurship and an obesity index. Very significant effects are found. If weexplain ? in a simple model where time discounting is ignored, we find completely differentestimates for ? . We conclude that in the case of lotteries with big prizes a simultaneous estimateof ? and ? is needed in order to avoid misspecification.
Keywords: D12; D80; D90; E21; 330; Expected Utility; Risk Aversion; Time Preference; Lotteries; Hypothetical Questions.; Glücksspiel; Erwartungsnutzen; Risikoaversion; Zeitpräferenz; Test; Theorie; Niederlande